Effect of non-genetic factors on growth performance of Brahman crossbred cattle of Bangladesh - Mahbubul, Mohammad; Hoque, Md Azharul (Fundamental and Applied Agriculture, 2020)
The study was conducted to investigate the effects of non-genetic factors (sex, season and agro-ecological zone) on growth performance of Brahman crossbred cattle population of Bangladesh. Data on 5662 Brahman crossbred (50%) calves were collected from the herdbook maintained by the Depart- ment of Livestock Services and Department of Animal Breeding and Genetics of Bangladesh Agricultural University across eight location and four agro- ecological zone of the country from January 2014 to November 2018. Least squares means were analyzed using General Linear Model (GLM) of Statistical Analyses System (SAS). Sex had significant (p<0.001) effect on birth weight, weight at one-, three-, nine-, twelve- and twenty-four month, ADG from 6- to 9-month and from 9- to 12-month of age. However, sex effect was non-significant for 6-month body weight, ADG from birth to 3-month and ADG from 3- to 6-month. Season effect was significant (p<0.001) on almost all growth traits considered in this study except 12-month and 24-month body weight. Agro-ecological zones had significant (p<0.001) effect on birth weight, weight at one-, three-, nine-, twelve- and twenty-four month, ADG from 3- to 6-month and ADG from 6- to 9-month of age. In contrary, ADG from birth to 3-month and ADG from 9- to 12-month were not significantly (p<0.001) affected by agro-ecological zones. It revealed from the present study that difference in management practices by farmers and agro-ecological zones in Bangladesh should be taken into account in formulating beef breeding program.